Investigating the Effect of Processing Parameters on the Products of Hydrothermal Carbonization of Corn Stover - Mohammed, Ibrahim Shaba; Kushima, Keisuke; Shimizu, Naoto (Sustainability, 2020)
Corn stover is an abundant and underused source of lignocellulose waste biomass that can be transformed into a high-quality energy resource using hydrothermal carbonization (HTC). This investigation has focused on the effect of processing parameters on the products of HTC—namely solid fuel or hydrochar and liquid and gas fractions. HTC was conducted in a temperature-controlled small batch reactor with corn stover and deionized water under oxygen-free conditions obtained by pressurizing the reactor headspace with nitrogen gas. The properties of the hydrochar and liquid and gas fractions were evaluated as a function of the process temperature (250–350 °C), residence time (30–60 min) and biomass/water ratio (0.09–0.14). Central composite design modules in a response surface methodology were used to optimize processing parameters. The maximum mass yield, energy yield and high heating value (HHV) of the hydrochar produced were 29.91% dry weight (dw), 42.38% dw and 26.03 MJ/kg, respectively. Concentrations of acetic acid and hydrogen gas were 6.93 g/L and 0.25 v/v%, respectively. Experimental results after process optimization were in satisfactory agreement with the predicted HHV. The optimal HTC process parameters were determined to be 305 °C with a 60 min residence time and a biomass/water ratio of 0.114, yielding hydrochar with a HHV of 25.42 MJ/kg. The results confirm the feasibility of an alternative corn stover management system.